2001
DOI: 10.1111/j.1600-0773.2001.880509.x
|View full text |Cite
|
Sign up to set email alerts
|

Nimesulide Aggravates Kainic Acid‐Induced Seizures in the Rat

Abstract: Treatment of rats with kainic acid (10 mg/kg, intraperitoneally) triggers limbic seizures. Cyclooxygenase‐2 mRNA is expressed in the hippocampus and cortex after 8 hr and marked cell loss occurs after 72 hr in the CA1‐CA3 areas of the hippocampus. We examined the effect of the cyclooxygenase‐2 inhibitor, nimesulide (N‐(4‐nitro‐2‐phenoxyphenyl)‐methanesulfonamide), on kainate‐induced seizures and delayed neurotoxicity. Nimesulide (10 mg/kg, intraperitoneally) was well tolerated given alone or 6–8 hr after kaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Following basal recording, rats were administered KA (10 mg kg 21 ; Sigma-Aldrich, Gillingham, UK) dissolved in saline to induce increased excitatory activity (Kunz and Oliw, 2001;Westbrook and Lothman, 1983). Separate groups of rats were injected with the FAAH inhibitor URB597 (Alexis Biochemicals, Lausen, Switzerland) at doses of 0.3 mg kg 21 (n 5 5 rats) or 1 mg kg 21 [n 5 5 rats; dissolved in 5% EtOH/5% Cremophor EL (Fluka Biochemika, Buchs, Switzerland)/90% saline, (v/v %)], or with vehicle (n 5 5 rats), coadministered with KA.…”
Section: Recording Proceduresmentioning
confidence: 99%
“…Following basal recording, rats were administered KA (10 mg kg 21 ; Sigma-Aldrich, Gillingham, UK) dissolved in saline to induce increased excitatory activity (Kunz and Oliw, 2001;Westbrook and Lothman, 1983). Separate groups of rats were injected with the FAAH inhibitor URB597 (Alexis Biochemicals, Lausen, Switzerland) at doses of 0.3 mg kg 21 (n 5 5 rats) or 1 mg kg 21 [n 5 5 rats; dissolved in 5% EtOH/5% Cremophor EL (Fluka Biochemika, Buchs, Switzerland)/90% saline, (v/v %)], or with vehicle (n 5 5 rats), coadministered with KA.…”
Section: Recording Proceduresmentioning
confidence: 99%
“…It has been reported that the pretreatment of COX-2 inhibitors including celecoxib aggravated kainic acidinduced seizure activity in rodents and aggravated kainic acid-induced neuronal death in the hippocampus (Baik et al, 1999). The broad COX inhibitor such as ibuprofen caused deficits in spatial learning in a water maze (Shaw et al, 2003), whereas several reports showed the post-treatment of COX-2 inhibitors restored the memory deficit and learning behaviors and prevented seizure-induced neuronal death (Gobbo and O'Mara, 2004;Kunz and Oliw, 2001a;2001b). The effects of COX-2 inhibitors on the PTZ-induced seizures are also controversial; Dhir and coauthors reported the anticonvulsant effect of COX-2 inhibitors (Dhir and Kulkarni 2006;Dhir et al, 2006a), while Akasura and coauthors showed that COX-2 inhibitors have neither anticonvulsant nor proconvulsant effects on PTZ-induced seizures (Akarsu et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…PGE2 activated on the electroencephalogram, while prostaglandin E1inhibit pentylenetetrazole-induced convulsions in rats (Kim et al, 2008). The drugs that inhibit COX-2 activity, such as indomethacin and selective COX-2 inhibitors, could reduce hippocampal cell death and seizure frequencies in several animal models of epilepsy (Jung et al, 2006;Kunz and Oliw, 2001a;Shafiq et al, 2003). Thus, drugs that reduce the production of PGs may have useful therapeutic effects in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Different drugs with anticyclooxygenase (COX) activity, such as indomethacin, aspirin and nimesulide, could either inhibit or exacerbate seizures. This is likely a result of the specific actions of COX inhibitors on the basal production of the various prostaglandins and also on the different profiles of prostaglandins produced by different seizure models [80,81]. Glucocorticoids have been demonstrated to be proconvulsant if given in large amounts in the kainate model [82].…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 97%